Green Accounting, ESG, Komisaris Independen dan Pengaruhnya terhadap Kinerja Keuangan - Linova Angesti Hartono; Aurora Angela (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose – This study aims to examine the effect of green accounting, ESG, and independent commissioners on corporate financial performance. Method – This research applies a quantitative approach using multiple linear regression analysis. The studi observes all companies in Indonesia that have PROPER ratings, ESG score from Refinitiv, and independent board structures during the 2020-2024 period. Main Findings – The result indicate that ESG has a positive and significant effect on financial performance. In contrast, green accounting and independent commissioners do not have a significant impact on financial performance. These findings highlight that ESG disclosure serves as an effective sustainability strategy for enhancing profitability. Theory and Practical Implications – Theoretically, the result support legitimacy and stakeholder theories, which emphasize the importance of transparency and responsible corporate governance. Practically, this studi suggest that companies should strengthen ESG practices to increase investor trust and financial outcomes. Novelty – The novelty of this research lies in utilizing all Indonesian companies with ESG scores, as well as using the latest data in the Indonesian context for the period 2020-2024 and adding references from the latest research.